2020
DOI: 10.1039/d0cp00111b
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of trivalent cations in NaX zeolite nanocrystals for the adsorption of O2 in the presence of CO2

Abstract: Competative adsorption of O2 and CO2 in FAU zeolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…While the band area corresponding to the adsorbed CO2 from the pure gas and carbogen is similar due to the same concentration delivered to the sample (see experimental section). Additionally, our theoretical studies showed that a strong affinity of FAU-type zeolites towards O2, even in the presence of CO2, is expected [34].…”
Section: Physicochemical Characterizations Of Nanosized Zeolitesmentioning
confidence: 73%
“…While the band area corresponding to the adsorbed CO2 from the pure gas and carbogen is similar due to the same concentration delivered to the sample (see experimental section). Additionally, our theoretical studies showed that a strong affinity of FAU-type zeolites towards O2, even in the presence of CO2, is expected [34].…”
Section: Physicochemical Characterizations Of Nanosized Zeolitesmentioning
confidence: 73%
“…The ion-exchange was performed two times with a 0.03 mM of Gd(NO 3 )•6H 2 O solution and 5 ml of 2.5 wt% of K-LTL zeolite as described elsewhere. 17 The resulting Gd-exchanged LTL zeolite was purified with water and finally stored in the form of a colloidal suspension in an aqueous solution.…”
Section: Synthesis Of Ltl Nanocrystalsmentioning
confidence: 99%
“…12,16 For instance, the CO 2 and O 2 sorption properties of faujasite (Na-FAU-X) were controlled by partial ion-exchange of the sodium extra-framework cations by trivalent metals (Gd 3+ , Ce 3+ ). 17 The high suspension stability and non-toxicity of nanosized FAU zeolite showed advantages as hyperoxic/hypercapnic gas carriers for glioblastoma treatment. 18 More recently, nanosized FAU zeolite with luminescent properties was developed, which enabled tracking the fate of zeolites in vitro experiments on cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility to obtain extra and intra-framework transition metal sites makes zeolites extremely versatile heterogenous catalysts [22][23][24]. In order to understand their reactivity, in-depth characterization is needed, and the combination of experimental and theoretical methods provide highly valuable information on the atomic level [25][26][27].…”
Section: Introductionmentioning
confidence: 99%